Radiocarbon, Tephra, and Paleomagnetic Data from 5 Northern North Atlantic Sediment Cores to support Reilly et al. 2023, "The Amplitude and Timescales of 0-15 ka Paleomagnetic Secular Variation in the Northern North Atlantic." ... - Reilly, Brendan; Stoner, Joseph; Ólafsdóttir, Sædís; Jennings, Anne; Hatfield, Robert; Kristjánsdóttir, Gréta Björk; Geirsdóttir, Áslaug (Zenodo, 2023)
Data in support of Reilly et al., 2023, "The Amplitude and Timescales of 0-15 ka Paleomagnetic Secular Variation in the Northern North Atlantic." Published in the Journal of Geophysical Research: Solid Earth. Excel file includes worksheets for the following data: Tabular versions of the Supplementary Data Tables from the associated publication: Supplementary Table S1 from Publication: 14C data from sediment cores used in study Supplementary Table S2 from Publication: 14C data used in the GREENICE15 Stack Supplementary Table S3 from Publication: Tephra data used in study Paleomagnetic Datasets for the Characteristic Remanent Magnetizations used in this study: Paleomagnetic Data for Core MD99-2264 Paleomagnetic Data for Core MD99-2265 Paleomagnetic Data for Core MD99-2266 Paleomagnetic Data for Core MD99-2269 Paleomagnetic Data for Core MD99-2322 Independent radiocarbon based Age Models for 5 cores used in this study: Independent Age Model for Core MD99-2264 Independent Age Model for Core MD99-2265 Independent ... : This work was supported by National Science Foundation awards EAR-1645411 and OCE-2300114. ...